2022
DOI: 10.1590/1516-3180.2021.0200.r1.03052021
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis on efficacy of convalescent plasma in acute respiratory distress syndrome due to COVID-19

Abstract: BACKGROUND: Coronavirus disease 2019 (COVID-19) is an ongoing global health threat. However, currently, no standard therapy has been approved for the disease. OBJECTIVES: To evaluate the clinical effectiveness of convalescent plasma (CP) in patients with acute respiratory distress syndrome (ARDS) due to COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The change in ferritin levels, on the other hand, was not found to be significant. However, in another study, no significant difference was found in CRP, d-dimer, lymphocyte, ferritin and procalcitonin values before and after immune plasma treatment (13). In the same study, no significant difference was found in ALT, AST, and fibrinogen levels; Similarly, no significant difference was found in ALT and fibrinogen levels in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…The change in ferritin levels, on the other hand, was not found to be significant. However, in another study, no significant difference was found in CRP, d-dimer, lymphocyte, ferritin and procalcitonin values before and after immune plasma treatment (13). In the same study, no significant difference was found in ALT, AST, and fibrinogen levels; Similarly, no significant difference was found in ALT and fibrinogen levels in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…The process of study selection is represented in the Preferred Reporting Items for Systematic Reviews and Meta-analyses flow diagram ( Figure 1 ). Thirty-nine RCTs 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 enrolling 21,529 participants and 70 matched cohort studies 2 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , ...…”
Section: Resultsmentioning
confidence: 99%
“…As of December 2020, the therapeutic agents approved for COVID-19 in Japan were limited to two drugs: remdesivir, an antiviral drug, granted a Special Approval for Emergency on 7 May 2020, and dexamethasone, which has an anti-inflammatory effect. Several case reports and clinical studies of convalescent plasma therapy have been reported [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], but the results have been conflicting. This could have occurred because the neutralizing antibody titer in the COVID-19 convalescent plasma administered was not measured in most studies, and there appears to be an association between a higher antibody index and severe COVID-19 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%